THE EFFECTS OF EXTENSIVE READING ON EFL UNIVERSITY STUDENTS’ READING COMPREHENSION AND READING RATE - Tran Thi Ngoc Yen*, Nguyen Thi Kim Anh, Nguyen Viet Hung (Tạp chí Khoa học)
Extensive reading has been recognized as an alternative method to develop reading fluency. However, within the context of English language teaching in Vietnam, there has not been much research that examines the benefits of this method for university students. This study explores the effects of extensive reading on EFL university students’ reading comprehension and reading rate. The data were collected through an experiment conducted over 15 weeks. The participants were students following English programs at a university in Vietnam. Five intact classes were randomly assigned to be the control group, and four other intact classes were randomly assigned to be the treatment group. A pre-test and a post-test were used to measure the participants’ reading fluency improvement. During the experiment, the treatment group engaged in approximately 100 minutes of extensive reading weekly, using English stories suitable to their vocabulary levels, while the control group were given intensive reading activities. The results revealed significant reading comprehension and rate increases among the treatment group. The findings have highlighted the benefits of integrating extensive reading into English language teaching curricula and emphasized the importance for educators and students to recognize its role in enhancing English language learning.